A case of anorexia nervosa whose body image deteriorated after being weighed with classmates at school - Kaymaz, Nazan; Uzun, Mehmet Erdem (The European Research Journal, 2022)
Anorexia nervosa is an eating disorder characterized by a heightened desire to have a lean body structure that leads to an extreme fear of becoming fat. The patients with this disorder have a severely impaired perception of their bodies. Negative behaviors and attitudes in peer communication may hugely impact the affected individual at every stage of this disorder. The level of peer communication quality could be shaped by the conditions prevalent in the school, particularly the approaches undertaken by the educators and the staff at school. However, it would be incorrect to state that wrong communication styles adopted by the friends of an individual or unsuitable conditions in the school environment alone would be sufficient for the development of anorexia nervosa in adolescents. A 16-year-old girl with anorexia nervosa was followed up for 1.5 years after the diagnosis of the disorder, a period during which she had begun exhibiting improvement in her condition. However, her symptoms reappeared after she underwent height and weight measurements at school during the physical education and sports class to determine her physical health. This case is presented (1) to remind that anthropometric measurements are personal data and (2) to emphasize that it would be appropriate to provide privacy in this respect at schools.